A Research of Pyogenic Granuloma Genesis Factor With Immunohistochemical Analysis. Issue 8 (November 2017) - Park, Si Hyun; Lee, Jun Ho; Tak, Min Sung; Lee, Hyun Ju; Choi, Hwan Jun
Abstract : Abstract: Pyogenic granuloma (PG) is a type of vascular tumor for which the growth mechanism is poorly understood. Estrogen and progesterone may influence vascular malformations by increasing neovascularization in the lesions. Pregnancy tumor is a term for PG that occurs on the gingival mucosa of pregnant women in response to local irritation or injury. The etiology and pathogenesis of this phenomenon are not fully understood. Hormonal imbalance has been hypothesized to be responsible for the development of gingival hyper-reactive inflammatory responses. Moreover, it has been shown in vitro that the female sex hormone is a potential regulator of the production of several growth factors, such as vascular endothelial growth factor (VEGF), basic fibroblast growth factor, and nerve growth factor, in various cell types. Epidermal growth factor receptor (EGFR) is also involved in a signaling cascade that influences proliferation and other tumor-promoting activities, as well as the responsiveness to chemotherapy. The aim of this study was to examine the relationship between PG pathogenesis and hormone imbalance in 21 patients. All specimens were analyzed by immunohistochemical staining with hematoxylin and eosin for the following hormones: estrogen receptor, progesterone receptor, VEGF, and EGFR. The analysis of the specimens showed that estrogen receptor and EGFR were not associated with PG, while VEGF was statistically related to PG. In addition, there was no significantly difference between sex, tumor location, or pregnancy. There are few studies about correlation between the pathogenesis of PG and sex hormones or growth factors demonstrated via immunohistochemical analysis. The results of this study indicate that estrogen and progesterone do not influence the pathogenesis of PG; however, VEGF may be associated with the pathogenesis of PG.